Management system of traditional medicine in a social and semantic web platform : an approach based on a visual ontology - (:unkn) unknown (My University, 2018)
Traditional medicine (TM) is seen as a complementary health system to modern medicine (MM). This TM has the advantage of being easier to access, cheaper and more adapted to local specificities. However, African TM suffers from the lack of sharing and preservation of medical knowledge : the majority of practitioners speak local languages. They use non-codified languages, and many of them keep their knowledge secret. To facilitate knowledge preservation and communication between practitioners of TM (TMP) we aim at designing SysMEDTRAD, a system based on a domain ontology of TM and a visual ontology integrating an iconic language. This research work brings an innovative solution for practitioners of TM, not only to allow them to contribute continuously to the modernization and the explicit improvement of this medicine, but also to equip them with a tool to practice their healing art. More precisely, this work has focused on the construction of a domain ontology referred to as ontoCONCEPT-Term entirely terminological. It also includes an iconic language started on identifying medicinal plants. Traditional recipes and remedies have a diagrammatic representation. This language will have to be extended while following the princple drawn by a visual ontology approach, ontoICONE. Via this visual ontology, we can trenscand the barriers related to illiteracy, orality and the many local languages to the number of 1127 in West Africa, where this community web knowledge sharing project takes place. ontoICONE is partly terminological and iconic. This terminological part is common with ontoCONCEPT-Term. Those two entities ontoICONE and ontoCONCEPT-Term form ontoMEDTRAD.To build our ontology, we took inspiration from ontology construction methodologies, especially Diligent, NeOn and OntoForInfoScience. We have combined multiple sources of information and knowledge on TM, including repeated meetings with TMP in different regions, published works in biosciences (TM, ethn
Keywords: African Research